Evolution of obligate siblicide in boobies: 2: food limitation and parent-offspring conflict. - Anderson, D. J. (1990)
BIB Now: 167
English
461
Keywords: EV, BH, SU, EC -- Evolution of obligate siblicide in boobies: 2: food limitation and parent-offspring conflict. -- birds, boobies, sula, food limitation, parent offspring conflict -- aves, piqueros de patas azules, piqeros de patas rojas, piqueros enmascarados, limitación de alimento